Kindle Fire : Amazon's heated battle for the tablet market - Sawhney, Mohanbir S.; Owens, Joseph; Goodman, Pallavi ([London] : SAGE, 2016)
This case is intended to illustrate to readers the challenges faced in 2011-2013 by Amazon's CEO, Jeff Bezos, as he guided his company into the exploding tablet market. Faced with the tough decision between focusing on the e-reader market - which Amazon had come to dominate with its Kindle product line - and making a foray into tablets - for which it had no expertise - Bezos took the brave decision to chose the latter.
Originally Published in: Sawhney, M., Owens, J., & Goodman, P. (2014). Kindle Fire: Amazon's Heated Battle for the Tablet Market (revised 25/04/2014). 5-413-751. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Amazon.com (Firm); Kindle (Electronic book reader); Marketing -- Management -- Case studies; Brand name products -- Management -- Case studies; Branding (Marketing) -- Case studies